The Digital Radio Concentrator System - Moorhead, Simon (Journal of Telecommunications and the Digital Economy, 2019)
A reprint of a technical paper from 1986 which details the design and development of the Digital Radio Concentrator System deployed by Telstra to provide automatic telephone services throughout outback Australia.